Management Of Bilateral Cleft Lip And Palate In A New-Born By Presurgical Nasoalveolar Molding - Vasanth, Satish; Gnanam, Padmashini; Shankar, Ravi; Arjunan, Priyadharshini (Journal of Neonatal Surgery, 2025)
Management of cleft lip and palate involves a multidisciplinary approach including a team of doctors. The dental surgeons play a vital role in ensuring an outcome which is both esthetic and functionally advantageous to the patient. Presurgical infant orthopaedics was introduced in the 1950s as an adjunct to surgical procedures. Many modifications have been proposed to this concept. Presurgical Nasoalveolar molding technique manipulates the immature nature of the nasal cartilages and the alveolar bone to bring about changes in the morphology of the cleft lip and palate prior to surgery. This technique molds the nasal cartilages and the dentoalveolar arches and has many benefits. It decreases the need for secondary surgeries and the amount of scar tissue present is also negligible. In this article, we present a case of bilateral cleft palate with cleft lip in a new born baby, managed with Presurgical Nasoalveolar Molding before surgical correction.